Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 532 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Scinax squalirostris (Lutz, 1925)" ] } The dataset includes 532 records from 24 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0000402-160623103540712/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences